The Accounting Practices of Heritage Assets - Hassan, Nor Laili; Saad, Natrah; Ahmad, Halimah Nasibah; Salleh, Md. Suhaimi Md.; Ismail, Mohamad Sharofi (International Journal of Economics and Financial Issues, 2016)
Accrual-based accounting is introduced to the government agencies with the intention to hold prudent fiscal management and improve the efficiency of financial management and accounting of the Malaysian Government. For that purpose, Malaysian Public Sector Accounting Standards (MPSAS) was introduced as a main reference in applying the accrual-based accounting. MPSAS 17 which deals with heritage assets, will take effect in 2017. The study intended to discover how do overseas’ museums report their heritage assets. By doing so, it is hoped that a benchmark can be set for the local museums. The study found that the museums abroad are also facing problems in delivering good accounting practices. In case of museums in Malaysia, these issues can be tackled through specific legal provisions, benchmarking and well-established Standard Operating Procedures (SOP) in assisting museums to improve their reporting practices at par with reputable museums in overseas. Keywords: Accrual accounting; Heritage assets; Government JEL Classifications: M41; M48